EVALUASI SISTEM PENGENDALIAN MANAJEMEN DALAM MENGHADAPI PANDEMI COVID-19 PADA PT. JNE INDONESIA AGEN CIKUDA JATINANGOR - R. A Fadillah Aulliah Ibrahim (Universitas Sains dan Teknologi Komputer, 2021)
Setting a strategy in running the existing system in the company, therefore it is very important for the company to evaluate the management control system which is one of the basic functions of management. The object of the research is PT. JNE Indonesia, especially at Cikuda Jatinangor agents. This study aims to determine the state of the control system in JNE in the midst of the COVID-19 pandemic. The results of the study explain that the system that applies at JNE is still running well as evidenced by the absence of complaints from company employees, the implementation of activities that run normally, and the programs that are run in the midst of this pandemic do not make income decline JNE’s management performs the control systems very well, and ensures the security of packages that will be sent until they are received by costumers.